A general and facile one-pot process of isothiocyanates from amines under aqueous conditions - Sun, Nan; Li, Bin; Shao, Jianping; Mo, Weimin; Hu, Baoxiang; Shen, Zhenlu; Hu, Xinquan (Beilstein Journal of Organic Chemistry, 2012)
A general and facile one-pot protocol for the preparation of a broad range of alkyl and aryl isothiocyanates has been developed from their corresponding primary amines under aqueous conditions. This synthetic process involves an in situ generation of a dithiocarbamate salt from the amine substrate by reacting with CS2 followed by elimination to form the isothiocyanate product with cyanuric acid as the desulfurylation reagent. The choice of solvent is of decisive importance for the successful formation of the dithiocarbamate salt particularly for highly electron-deficient substrates. This novel and economical method is suitable for scale-up activities.
Keywords: aqueous conditions; cyanuric acid; isothiocyanates; one-pot process; organic synthesis; primary amines